Taxonomic implications of leaf epidermal characteristics in subfamily Caesalpinioideae (Leguminosae) - Pandey, Shivaraman; Chaudhary, Lal Babu; Singh, Lav; Srivastava, Ravi Prakash; Singh, Arpit; Msihra, Ajay Kumar; Dixit, Pooja; Saxena, Gauri (Phytotaxa, 2023)
This paper deals with the foliar epidermal anatomy of 25 species belonging to 14 genera (i.e., Bauhinia, Caesalpinia, Cassia, Delonix, Guilandina, Hardwickia, Libidibia, Lysiphyllum, Parkinsonia, Peltophorum, Phanera, Saraca, Senna and Tamarindus) of subfamily Caesalpinioideae (Leguminosae) using light microscopy (LM). The target species were collected from different regions (Terai Region, Gangetic Plain, Vindhyan Region and Semiarid region) of Uttar Pradesh, India. Several leaf micromorphological characters such as anticlinal wall pattern, epidermal cells shape, stomatal complex andtrichomes were assessed in the present study. Both quantitatively and qualitativelystudy revealed that species understudy mostly consisted of polygonal epidermal cells with straight anticlinal walls, were amphi stomatic with paracytic stomata, non-glandular and unicellular trichomes. An attempt was also made to establish phylogenetic relationships in members of Caealpinioideae growing in Uttar Pradesh on the basis of these characters.